Vitamin D, muscle function, and exercise performance - Bartoszewska, M.; Kamboj, M.; Patel, D. R. (Pediatric Clinics of North America, 2010)
Vitamin D has an important role in skeletal muscles. Previously recognized for its effects on bone, it is now known that vitamin D has a much wider spectrum of usefulness for muscle. Studies indicate that vitamin D deficiency is pandemic. Those affected include the young and otherwise healthy members of the population, including athletes. Controversy exists regarding the amount of supplementation required to reverse deficiency and the relative effect of such a reversal on overall health. This article reviews current data on the role of vitamin D on muscle function, and explores the potential implications of its deficiency and supplementation on physical fitness and athletic performance.